2014
DOI: 10.1007/978-3-319-13704-9_28
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Semantic Approach to Building Dynamic Maps of Research Communities

Abstract: Abstract. In earlier papers we characterised the notion of diachronic topicbased communities -i.e., communities of people who work on semantically related topics at the same time. These communities are important to enable topic-centred analyses of the dynamics of the research world. In this paper we present an innovative algorithm, called Research Communities Map Builder (RCMB), which is able to automatically link diachronic topic-based communities over subsequent time intervals to identify significant events.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…For example, the sudden appearance of a number of publications concerning a combination of previously uncorrelated topics may suggest that some pioneer researchers are investigating new possibilities and maybe shaping a new emerging area. In the same way, as pointed out in Salatino (2015), we can hypothesize a wide array of relevant dynamics that could anticipate the creation of a new research area, such as a new collaboration between two or more research communities (see for example Osborne et al (2014)), the creation of interdisciplinary workshops, a rise in the number of experts working on a certain combination of topics, a significant change in the vocabulary associated with relevant topics (Cano Basave et al 2016), and so on. This paper presents a study of some dynamics preceding the creation of novel topics which supports our hypothesis.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…For example, the sudden appearance of a number of publications concerning a combination of previously uncorrelated topics may suggest that some pioneer researchers are investigating new possibilities and maybe shaping a new emerging area. In the same way, as pointed out in Salatino (2015), we can hypothesize a wide array of relevant dynamics that could anticipate the creation of a new research area, such as a new collaboration between two or more research communities (see for example Osborne et al (2014)), the creation of interdisciplinary workshops, a rise in the number of experts working on a certain combination of topics, a significant change in the vocabulary associated with relevant topics (Cano Basave et al 2016), and so on. This paper presents a study of some dynamics preceding the creation of novel topics which supports our hypothesis.…”
Section: Introductionmentioning
confidence: 53%
“…Herrera et al (2010), Sun et al (2013), Nowotny et al (2013) suggested that the development of new topics is actually encouraged by the cross-fertilisation of established research areas and recognised that multidisciplinary approaches foster new developments and innovative thinking. Sun et al (2013) and Osborne et al (2014) provided empirical evidence to these theories by analysing the social dynamics of researchers and their effect on research communities and topics.…”
Section: Introductionmentioning
confidence: 99%
“…However, as pointed out by previous works [18], keywords tend to be noisy and do not always represent research topics. For example, Osborne et al [19] show that the use of a semantic characterisation of research topics yields better results for the detection of research communities.…”
Section: Related Workmentioning
confidence: 99%
“…For example, the sudden appearance of a 79 number of publications concerning a combination of previously uncorrelated topics may 80 suggest that some pioneer researchers are investigating new possibilities and maybe shaping a 81 new emerging area. In the same way, as pointed out in Salatino (2015), we can hypothesize a 82 wide array of relevant dynamics that could anticipate the creation of a new research area, 83 such as a new collaboration between two or more research communities (see for example 84 Osborne et al (2014)), the creation of interdisciplinary workshops, a rise in the number of 85 experts working on a certain combination of topics, a significant change in the vocabulary 86 associated with relevant topics (Cano Basave et al 2016), and so on. 87…”
mentioning
confidence: 93%
“…Herrera et al 59 (2010), Sun et al (2013), Nowotny et al (2013) suggested that the development of new 60 topics is actually encouraged by the cross-fertilisation of established research areas and 61 recognised that multidisciplinary approaches foster new developments and innovative 62 thinking. Sun et al (2013) and Osborne et al (2014) provided empirical evidence to these 63 theories by analysing the social dynamics of researchers and their effect on research 64 communities and topics. 65…”
mentioning
confidence: 99%